2019
DOI: 10.2174/1570162x17666190924195439
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Research Accessibility and Data Elements of HIV Registries

Abstract: Background:: Patient registries represent a long-term data collection system that is a platform for performing multiple research studies to generate real-world evidence. Many of these registries use common data elements (CDEs) and link data from Electronic Health Records. Objective:: This study evaluated HIV registry features that contribute to the registry’s usability for retrospective analysis of existing registry data or new prospective interventional studies. Methods:: We searched PubMed and ClinicalTr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Having assessed the absence of significant differences between the two methods, the authors believe that the electronic will over time substitute the paper form. It is possible to make this prediction since the distribution, collection and compilation of PROMs within electronic registers entails obvious advantages regarding logistics and data usability [26]. Several advantages can be obtained with the systematic use of electronic formats.…”
Section: Discussionmentioning
confidence: 99%
“…Having assessed the absence of significant differences between the two methods, the authors believe that the electronic will over time substitute the paper form. It is possible to make this prediction since the distribution, collection and compilation of PROMs within electronic registers entails obvious advantages regarding logistics and data usability [26]. Several advantages can be obtained with the systematic use of electronic formats.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al 4 , in a systematic review of the literature, identified 13 HIV registries, of which 61.5% are the product of a collaboration policy and 53.8% have a management process for requesting data collaboration, although there are shortcomings related to ethical support and research data 5 . In comparison, our registry contains all the key features for data collection like criteria for inclusion of participants (case definitions, data elements collected, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…A review by Craig et al aimed to assess the elements that make up a registry and whether they contain research data. This identified 13 HIV registries that include specific-registry information, collaboration processes and research data 5 . Examples of these registries or observational cohorts were EMBRACE (USA) 6 , CFAR Registry (USA) 7 , CCR/HIV of the VA Department (USA) 8 , San Francisco HIV/AIDS Surveillance Registry 9 , New York City HIV/AIDS Surveillance Registry 10 , Stiching HIV Monitoring in Netherlands 11 , HARS in Missouri 12 , Australian National HIV Registry 13 , InfCare HIV (Sweden) 14 , Minnesota HIV Surveillance Registry 15 , IeDEA (Rwanda) 16 and others 5,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…CDISC HIV therapeutic area user guide, published in January 2019, is the only relevant HIV-specific data element effort [3] (in addition to base SDTM elements, it highlights lab codes for CD4 count, LOINC codes for HIV viral load testing and mother-infant data linking among many other things). A study focused on data elements and data sharing for HIV registries was published by our team in 2019 [27]. There are, however, prior studies that are not specific to HIV and cover data elements and dictionaries for medicine in general.…”
Section: Related Workmentioning
confidence: 99%